2010
DOI: 10.1186/1471-2121-11-83
|View full text |Cite
|
Sign up to set email alerts
|

The individual-cell-based cryo-chip for the cryopreservation, manipulation and observation of spatially identifiable cells. II: Functional activity of cryopreserved cells

Abstract: BackgroundThe cryopreservation and thawing processes are known to induce many deleterious effects in cells and might be detrimental to several cell types. There is an inherent variability in cellular responses among cell types and within individual cells of a given population with regard to their ability to endure the freezing and thawing process. The aim of this study was to evaluate the fate of cryopreserved cells within an optical cryo apparatus, the individual-cell-based cryo-chip (i3C), by monitoring seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A good correspondence of these two parameters is demonstrated in normal cells (Afrimzon et al, 2010).…”
Section: Heterogeneous Changes Of Mitochondrial Membrane Potential (Mmentioning
confidence: 73%
“…A good correspondence of these two parameters is demonstrated in normal cells (Afrimzon et al, 2010).…”
Section: Heterogeneous Changes Of Mitochondrial Membrane Potential (Mmentioning
confidence: 73%
“…This device enabled the comparison between prefreezing and postthawing data at single-cell resolution. In a subsequent study, Afrimzon et al 83 demonstrated that the functional activity of U937 cells that were freeze-thawed on the i3C devices had no statistically significant difference from the control cells that were cryopreserved via conventional cryo-vials. Most importantly, the combination of the multiparametric analysis at a single-cell resolution and the optical and biological features of the device enabled the accurate determination of the functional status of individual cells and subsequent retrieval and utilization of the most valuable cells, which are highly desirable for on-chip cryopreservation of oocytes or embryos.…”
Section: Role Of Microfluidics In Cryopreservation Of Gametes and Embmentioning
confidence: 99%
“…Later, Deutsh et al and Afrimzon et al (Afrimzon et al, 2010; Deutsch et al, 2010) introduced an individual cell-based cryo-chip (i3C) with an array of picowells (Figure 8B), enabling individual cell cryopreservation, observation, and retrieval for the first time. Furthermore, i3C is compatible with commonly used, commercially available cryostage (MDBCS 600; Linkam Instruments, Tadworth, UK), which extends its application to include programmed freezing and thawing of cells on a chip.…”
Section: Cooling and Warming: Programmable Freezing And Vitrificationmentioning
confidence: 99%
“…(C) A microfabricated chip with an incubation microchamber, microfluidic channels, and microheaters for on-chip cell cryopreservation. Reproduced from (Afrimzon et al, 2010; Deutsch et al, 2010; Li et al, 2014; Li et al, 2010) with permission.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation